Komunikasi dan Human Relation Pemimpin Berbasis Agama, Filsafat, Psikologi, Sosiologi Pendidikan - Dewi Indrawaty; Asep Deni Normansyah; Dian Hidayati; Maesaroh Maesaroh; Sofyan Sauri; Faiz Karim Fatkhullah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
Humans in their lives always need other people, because apart from being individual beings, humans are also social beings. As individual beings, they are able to develop themselves, while as social beings, humans in their lives are gifted with the ability to interact. One of the effective forums for interacting with each other is the organization. In the organization, it is certain that there will be interaction, one of which is through communication. It aims to achieve the objectives to be achieved. Communication is a basic human need, and is one of the important elements in the success of an organization. In an educational organization, for example, it cannot run without the support of communication. Because, how is it possible to educate humans without communication, and teach humans without communication. In general, educational leadership plays a very important role in directing and moving educational organizations to achieve the expected goals. The various roles that must be carried out by a leader cannot be realized without communication. The nature of the organization is very dependent on how the personnel in the organization communicate. The better the quality of communication, the better the quality of the organization. An important aspect of communication is the potential of communication itself as a tool that can be designed by management to achieve organizational goals. The importance of communication can also be seen from the benefits for the organization including the functions of control, motivation, emotional disclosure and the provision of information for decision making. ABSTRAK Manusia dalam kehidupannya selalu membutuhkan orang lain, karena disamping sebagai makhluk individual manusia juga adalah makhluk sosial. Sebagai makhluk individual, mereka mampu mengembangkan dirinya sendiri, sedangkan sebagai makhluk sosial, manusia dalam kehidupannya dikaruniai kemampuan berinteraksi. Salah satu wadah yang efektif untuk saling berinteraksi adalah organisasi. Dalam organisasi dipastikan akan terjadi interaksi, yang salah satunya melalui komunikasi. Hal ini bertujuan mencapai tujuan yang akan dicapai. Komunikasi merupakan kebutuhan dasar manusia, dan termasuk salah satu unsur penting dalam keberhasilan suatu organisasi. Dalam organisasi pendidikan misalnya, tidak dapat berjalan tanpa dukungan komunikasi. Sebab, bagaimana mungkin mendidik manusia tanpa komunikasi, dan mengajari manusia tanpa adanya komunikasi. Secara umum, kepemimpinan pendidikan berperan sangat penting dalam rangka mengarahkan dan menggerakkan organisasi pendidikan untuk mencapai tujuan yang diharapkan. Beragam peran yang harus dijalankan oleh seorang pemimpin mustahil bisa diwujudkan tanpa adanya komunikasi. Hakikat organisasi sangat bergantung pada bagaimana personal yang ada dalam organisasi tersebut berkomunikasi. Semakin baik kualitas komunikasi maka semakin baik pula kualitas organisasi tersebut. Aspek penting dari komunikasi yaitu potensi dari komunikasi itu sendiri sebagai alat yang dapat dirancang manajemen untuk pencapaian tujuan organisasi. Pentingnya komunikasi juga dapat dilihat dari manfaat bagi organisasi meliputi fungsi pengendalian, motivasi, pengungkapan emosional dan penyediaan informasi untuk pengambilan keputusan.